Between-subject similarity of functional connectivity-based organization of the human periaqueductal gray related to autonomic processing - de Rijk, Mathijs M.; Janssen, Janine M. W.; Fernández Chadily, Susana; Birder, Lori A.; Rahnama’i, Mohammad S.; van Koeveringe, Gommert A.; van den Hurk, Job (Frontiers in Neuroscience, 2022)
The periaqueductal gray (PAG) is a brain stem area designated to play an essential role in lower urinary tract (LUT) control. Post-mortem human and animal studies have indicated that the PAG is symmetrically organized in functionally and anatomically distinct columns which are involved in sympathetic or parasympathetic autonomic control of the LUT. The current study aims to find consistency across subjects and identify homologous clusters between subjects. Here, we evaluated data from 10 female participants. During a bladder filling protocol, we ran a resting-state functional magnetic resonance imaging (fMRI) scan while participants experienced a strong desire to void. A voxel-by-voxel correlation matrix of the PAG was created and parcellated using the Louvain module detection algorithm. Resulting in a map of the PAG in which each voxel is assigned to a cluster as determined by the Louvain module detection algorithm. The spatial similarity of resulting clusters between participants was assessed by computing the Dice similarity coefficient for all cluster comparisons. Next, we designed a permutation test to create randomized parcellation maps which enabled us to statistically test the similarity values observed across participants. We observed several significantly similar clusters between subjects compared to permutations (p ≤ 0.05). These results show that the PAG can be parcellated into distinct clusters which show a similar spatial distribution at the group level. This analysis is a crucial step to determine the agreement between in vivo PAG parcellations and the functional and anatomical columnar organization of the PAG which is known from previous research. These advancements may enable us to identify the relationship between LUT symptoms, such as urgency, and activity patterns in the PAG in normal and pathological states.